The effect of fabric’s structure on the breathability and the drying rate Properties - Chakroun, Mohamed Ghaith; Benltoufa, Sofien; Fayala, Faten (Communications in Development and Assembling of Textile Products, 2021)
Many parameters affect sportswear comfort. Therefore, we selected five sportswear fabrics designed for jogging and hiking T-shirts to study their structural characteristics and to investigate the influence of these characteristics on the clothing comfort properties. The areal weight, the thickness, the loop length and the course and wales densities were calculated. Investigations were performed on air permeability, water vapor resistance and drying time/rate properties of selected fabrics. We found that an increase in the mass per square meter and in thickness decreases the air permeability and increases the water vapor resistance of knitted fabrics. The air permeability is proportional to the loop length, while the water vapor resistance is inversely proportional to the loop length. Finally we did not find any significant relation between the fabric’s structure characteristics and the drying time/rate.